An anthology of decorated papers : a sourcebook for designers - Marks, P. J. M.; British Library (London: Thames & Hudson, 2015)
This remarkable and beautiful book brings together a collection of decorated papers dating from the 16th to the 20th century. They were produced for a wide variety of uses: as wrappers and endpapers for books, as the backing for playing cards, and even as linings for chests and cases. Some decorated papers were used as humble pictures for display in churches and the home; some were sold as souvenirs to pilgrims; and others were used merely as wrappings for foodstuffs such as gingerbread and chocolate. What unites all the papers in the book is the richness of their ornamentation and the thin, flexible characteristics of the original sheets. They are all further united by having been collected by Olga Hirsch (1889-1968), a trained bookbinder who left her collection of some 3,500 papers to the British Library, where they remain one of the largest and most diverse collections of decorated papers in the world. The collection has never previously been published except as a mini-format 64-page introductory gift book. This new beautifully designed album of the best and most exquisite papers in the collection will be a revelation and an inspiration to designers, bibliophiles and anyone with a love of pattern and ornamentation.
Hand-marbled papers -- Paste papers -- Brocade papers -- Block-printed papers -- Mass production: the nineteenth century and beyond -- Miscellaneous decorating techniques -- Glossary.
"British Library."
Includes bibliographical references and index.
Keywords: British Library; Artet boterore; Arti vizual-vizatimi-piktura; Decorative paper -- Pictorial works-punime figurative -- Letra dekorative; Marbled papers -- Pictorial works. -- Letra te mermerizuara; Decorative paper. -- Letra dekorative; Marbled papers. -- Artiste boterore; Papier; Ornament -- Ornamente-zbukurime; Marmorpapier -- Leter mermeri; Angli; Arti vizual-dekorimet artizanale-vizatimi-letra murale-letra mermeri-zbukurimet; Illustrated works; Pictorial works; Illustrated works